Reducing adult cardiac surgical site infections and the economic impact of using multidisciplinary collaboration. Issue 4 (December 2018) - Chiwera, L.; Wigglesworth, N.; McCoskery, C.; Lucchese, G.; Newsholme, W.
Summary: Background: Cardiac surgical site infections (SSIs) have devastating consequences and present several challenges for patients and healthcare providers. Adult cardiac SSI surveillance commenced in 2009 at our hospitals, Guy's & St Thomas' NHS Foundation Trust, London, as a patient safety initiative amid reported increased incidence of SSIs. Before this time, infection incidence was unclear because data collection was not standardized. Aim: To standardize SSI data collection and establish baseline SSI rates to facilitate deployment of evidence-based targeted interventions within clinical governance structures to improve quality, safety, and efficiency in line with our organizational targets. Methods: We standardized local data collection protocols in line with Public Health England recommendations and identified local champions. We undertook prospective SSI surveillance collaboratively to enable us to identify potential practice concerns and address them more effectively through a series of initiatives. Clinical staff completed dedicated surveillance forms intraoperatively and postoperatively. Findings: Overall adult cardiac SSI rates fell from 5.4% in 2009 to 1.2% in 2016 and coronary artery bypass graft rates from 6.5% in 2009 to 1.7% in 2016 ( P < 0.001). Gram-negative bacteria were recognized as important SSI causative organisms and were better controlled after introducing stringent infection control measures. Conclusion: Comprehensive, evidence-based infection control practices were successfully implemented through a multidisciplinary collaborative approach, which may have great potential to reduce Gram-negative, Staphylococcus aureus, polymicrobial and overall SSI burden and/or associated costs. We now investigate all SSIs using an established SSI detailed investigation protocol to promote continual quality improvement that aligns us perfectly with global efforts to fight antimicrobial resistance.